Evidence for dental caries decline among children in an East European country (Hungary) - Szo¨ke J, Petersen PE (Blackwell Synergy, 2000)
In Central and Eastern Europe oral health systems are in transition due to the economic and political changes. The aim of the present study was to highlight the long-term trend in dental caries prevalence of Hungarian children. A WHO National Pathfinder Survey of oral health status was conducted in 1996 which included 6-year-olds (n½900) and 12-year-olds (n½900). Similar surveys were performed in 1985 (age 6–7, n½895; age 12, n½893) and in 1991 (age 5–6, n½ 898; age 12, n½898) and the surveys were based on the same sites and examination criteria. Clinical data were collected by trained dental examiners according to the WHO Basic Methods. In 1996, 73% of 5–6-year-olds and 84.5% of 12-yearolds were affected by dental caries.